Effects of vitamin D supplementation on 24-hour blood pressure in patients with low 25-hydroxyvitamin D levels: a randomized controlled trial - Theiler-Schwetz, Verena; Trummer, Christian; Grübler, Martin R.; Keppel, Martin H.; Zittermann, Armin; Tomaschitz, Andreas; Karras, Spyridon N.; März, Winfried; Pilz, Stefan; Gängler, Stephanie (Nutrients, 2022)
Accumulating evidence suggests that potential cardiovascular benefits of vitamin D supplementation may be restricted to individuals with very low 25-hydroxyvitamin D (25(OH)D) concentrations; the effect of vitamin D on blood pressure (BP) remains unclear. We addressed this issue in a post hoc analysis of the double-blind, randomized, placebo-controlled Styrian Vitamin D Hypertension Trial (2011-2014) with 200 hypertensive patients with 25(OH)D levels <30 ng/mL. We evaluated whether 2800 IU of vitamin D3/day or placebo (1:1) for 8 weeks affects 24-hour systolic ambulatory BP in patients with 25(OH)D concentrations <20 ng/mL, <16 ng/mL, and <12 ng/mL and whether achieved 25(OH)D concentrations were associated with BP measures. Taking into account correction for multiple testing, p values < 0.0026 were considered significant. No significant treatment effects on 24-hour BP were observed when different baseline 25(OH)D thresholds were used (all p-values > 0.30). However, there was a marginally significant trend towards an inverse association between the achieved 25(OH)D level with 24-hour systolic BP (−0.196 per ng/mL 25(OH)D, 95% CI (−0.325 to −0.067); p = 0.003). In conclusion, we could not document the antihypertensive effects of vitamin D in vitamin D-deficient individuals, but the association between achieved 25(OH)D concentrations and BP warrants further investigations on cardiovascular benefits of vitamin D in severe vitamin D deficiency.
Gesehen am 18.05.2022